Bottlenecks and predictors of coverage and adherence outcomes for a micronutrient powder program in Ethiopia. (17th October 2019) - Tumilowicz, Alison; Habicht, Jean‐Pierre; Mbuya, Mduduzi N.N.; Beal, Ty; Ntozini, Robert; Rohner, Fabian; Pelto, Gretel H.; Fisseha, Tezera; Haidar, Jemal; Assefa, Nigussie; Wodajo, Hana Yemane; Wolde, Telahun Teka; et al.
Abstract: A theory‐driven evaluation was conducted to assess performance of a trial to deliver micronutrient powder (MNP) through the Ethiopian Ministry of Health. We adapted an approach to coverage assessment, originally developed to identify bottlenecks in health service delivery, to examine sequential program outcomes and their correlates using cross‐sectional survey data of caregivers of children 6–23 months ( N  = 1915). Separate multivariable Poisson regression models were used to estimate adjusted risk ratios of conceptually relevant determinants of coverage and adherence. Caregivers of children >11 months were more likely to have received MNP than caregivers of younger infants, yet children 12–17 months were 32% ( P  < 0.001) and children 18–23 months 38% ( P  < 0.001) less likely to have been fed MNP in the 14 days preceding the survey than children 6–11 months. Among caregivers who initiated feeding MNP, the most frequently reported reasons for discontinuing use were not obtaining additional supply (36.1%) and perceived child rejection of food with MNP (22.9%). For each additional time a caregiver met with frontline workers in the 3 months preceding the survey, they were 13% more likely to have recently fed MNP ( P  < 0.001). Caregivers' perception that MNP produced positive changes in children was associated with a 14% increase in the likelihood of having recently fed it ( P  < 0.001). These results emphasize the importance of counselling for MNP and infant and young child feeding for initial use and the importance of multiple contacts with frontline workers for continued use.